Attitudes, risk behaviour and noise exposure among young adults with hearing problems: identifying a typology - Hunter, Abby (Thieme Publishing, 2017)
This study explored attitudes towards leisure noise and use of hearing protection, and perceived susceptibility to leisure noise damage in young adults with hearing problems. Twelve participants aged between 18 and 35 years took part in a semi-structured interview. Data were analysed using Framework Analysis. The results showed a positive attitude to noise and a passion for loud music, along with a lack of knowledge of the consequences of noise damage; and perceived low risk of hearing problems were associated with people not using earplugs. The aesthetics, comfort, perceived effects on music quality; and attitude of others were all barriers to earplug use. Of those who had used earplugs, previous hearing-related symptoms and concern about future hearing damage were the main motivators for use. Four types of people were identified to describe the variation in attitudes and behaviours: There were those who had no change in behaviour or concern about damage; those who were concerned and used earplugs; those who were concerned and avoided loud venues; and those who were concerned about communication difficulties only. Considering the wide variability, it may be more effective to shift attention from trying to change individual attitudes and behaviours, to considering systemic changes to protect hearing, through ensuring the music industry and relevant authorities take greater responsibility.